Taxonomic study of the typhlocybine leafhopper genus Alebroides Matsumura (Hemiptera: Cicadellidae) in China - Qin, Dao-Zheng; Zhang, Ya-Lin (Zootaxa, 2011)
The present paper treats 20 species of the typhlocybine genus Alebroides Matsumura from China, among which two species new to science are described: A. parafuscus n. sp. and A. muzitaneus n. sp.; three new synonymies are reported: A. aurantinus Cai & Shen, 1999 is a junior synonym of A. rubicundus Ishihara, 1953; A. taibaiensis Chou & Zhang, 1987 is a junior synonym of A. yanglinginus Chou & Zhang, 1987 and A. qinlinganus Chou & Zhang, 1987 is a junior synonym of A. falcatus Sohi & Dworakowska, 1979; five species are new records for China. A key to all Chinese Alebroides species is provided, including 6 species reported occuring in China with specimens unavailable for this study except A. shokanus Matsumura.